VALIDITY AND RELIABILITY OF THE NEW STUDENT ADMISSION SYSTEM QUALITY QUESTIONNAIRE IN POSTGRADUATE PROGRAMS - Puspila, Ni Ketut Wike; Khamidi, Amrozi; Sholeh, Muhamad (STKIP Citra Bakti, 2026)
This study aims to evaluate the quality of new student admission services and develop a reliable and valid questionnaire to measure four key constructs: admission system quality, intention to apply, prospective student satisfaction, and initial academic service effectiveness. Instruments used in this context often lack psychometric evidence, raising concerns about their reliability and accuracy. The questionnaire was developed through item generation based on theoretical reviews, expert validation, and a pilot test involving 34 postgraduate prospective students. Validity was assessed using Corrected Item–Total Correlation with reference to critical r values, while reliability was evaluated with Cronbach’s Alpha, which showed a very high internal consistency (? = 0.992). These results confirm strong preliminary validity and reliability. Further validation through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) is planned for future studies with larger and more diverse samples to assess the instrument's factorial structure and model fit. The pilot test revealed that all 88 items exceeded the critical r threshold, confirming preliminary validity. However, the sample size and context limit generalizability, and future research should involve larger and more varied samples, as well as cross-institutional testing, to strengthen construct stability. This instrument can be effectively used for data-driven evaluation and quality improvement of student admission services in higher education institutions. It provides administrators with a reliable tool to enhance admission service delivery.